The Effect of Employee Competence and Engaging Leadership On Sales Target Through Motivation - Benni Sutanto; Desmon Sharon (CV Putra Publisher, 2026)
This study aims to analyze the influence of employee competence and engaging leadership on sales targets through motivation at PT Victory International Futures Pekanbaru. The population in this study was all 124 marketing employees working at PT Victory International Futures Pekanbaru. Data collection was conducted through questionnaires. The analytical tool used was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results of the study indicate that employee competence has a significant positive effect on sales targets. Engaging leadership has a positive and significant effect on sales targets. Employee competence has a positive and significant effect on motivation. Engaging leadership has a positive and significant effect on motivation. Motivation has a positive and significant effect on sales targets. Employee competence has a positive and significant effect on sales targets through motivation. Engaging leadership has a positive and significant effect on sales targets through motivation